1991
DOI: 10.2307/1966641
|View full text |Cite
|
Sign up to set email alerts
|

The Situation Analysis Study of the Family Planning Program in Kenya

Abstract: A new, relatively "quick and clean" operations research approach called a "situation analysis" was developed for examining the strengths and weaknesses of the family planning program of Kenya. Field research teams visited a stratified random sample of 99 of the Ministry of Health's approximately 775 service delivery points. Observation techniques and interviewing were used to collect information on program components and on the quality of care provided to new family planning clients during the observation day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…In a study carried out in urban and rural areas of Khartoum state, contraceptive pills were the most frequently used method, followed by intrauterine devices and injections (Ibnouf et al 2007). In Kenya, the most frequently used method was contraceptive pills, followed by injectables and IUDs (Miller et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in urban and rural areas of Khartoum state, contraceptive pills were the most frequently used method, followed by intrauterine devices and injections (Ibnouf et al 2007). In Kenya, the most frequently used method was contraceptive pills, followed by injectables and IUDs (Miller et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Kenya’s first nationwide assessment of family planning quality was conducted in 1989 among 99 randomly selected public facilities; this study found several deficiencies in service quality including restricted choice of methods, little information on management of side effects, failure on the part of providers to ascertain the client’s reproductive goals, and a dearth of mechanisms in place to ensure follow-up [10]. Results from a subsequent study in 1993, focusing on public facilities in Nairobi, did not differ markedly from the national study [11].…”
mentioning
confidence: 99%
“…The need for systematic, reliable, and relatively fast measures of quality gave rise to the development of a set of instruments known as the Situation Analysis (Simmons and Elias, 1994). As the first attempt to operationalize the concept of quality (Miller et al, 1991), the objectives of the situation analysis were to describe both the quality and infrastructure of family planning services and to evaluate the impact of quality on the outcomes of client satisfaction, realization of reproductive goals, contraceptive prevalence, and fertility (Fisher et al, 1992). …”
mentioning
confidence: 99%
“…The Hawthorne effect results during third party observations for which providers display their “best behavior” (MEASURE Evaluation, 2001, Bessinger and Bertrand, 2001). For example, during a situation analysis conducted in Kenya in 1991, a provider reported, “I usually do not have this much time for clients, but in view of your presence, I had better try to do an especially good job ” (Miller et al, 1991). Lastly, when interviewing family planning clients just before they exit the health facility, clients may have difficulty recalling the information that they received during their family planning counseling session, resulting in recall bias.…”
mentioning
confidence: 99%